STUDI TENTANG PERILAKU BURUK PADA PESERTA DIDIKKELASVISDIT WISATA HASANAH PONTIANAK - Asmarita, Asmarita; Yuline, Yuline; fergina, Ana (Universitas Tanjungpura, 2023)
This study aims to describe the bad behavior of several sixth grade studentsat SDIT Wisata Hasanah Pontianak. The method used is descriptive in theform of qualitative research. Sources of data are three grade VI students at SDIT Wisata Hasanah Pontianak, homeroom teachers, parents,and friends of the research subjects. Data collection techniques used are redirect communication techniques through interviews and documentation studies in the for mofcasenotes.Data analysis consisted of data reduction,data presentation, and conclusion drawing. The results showed symptoms of bad behavior, namely social aggressiveness such as often fighting or hitting, andusing dirty words, disobedient behavior such as frequently, rarely doing the assignments given by the teacher and the teacher's attention, irresponsibility such as often doing and not doing assignments. given by the teacher andoften come late to school. The causal factors are internal factors that are lessable to control emotions and lack a sense of responsibility, external factorsare the condition of the family environment. What homeroom teachers do rsare the condition of the family environment. What homeroom teachers do to help students have bad behavior is by assessing parents, giving advice and effort storeprimand.Cooperation between teachers and parentsis expectedtoreducebad behavior thatoccurs instudents